Enhanced photocatalytic activity of silver deposited on mesoporous carbon nitride for removal of phenol and aniline - Yuliati, Leny (2015)
In this study, mesoporous carbon nitride (MCN) as a visible light-driven photocatalyst was used to remove phenol and aniline as the models of organic pollutants. The MCN was successfully prepared via thermal polymerization of cyanamide. XRD patterns and FTIR spectra confirmed the successful formation of graphitic carbon nitride. The prepared MCN showed a larger percentage removal of phenol (18.6%) than that of aniline (12.7%). In order to improve the photocatalytic activity ofMCN, silver (Ag) was added via photodeposition method. The activity of MCN increased from 18.6% to 27.2% for removal of phenol on Ag/MCN (ratio 1:1) photocatalyst and from 12.7% to 19.8% for removal of aniline on Ag/MCN (ratio 1.5:1) photocatalyst. This study showed the role of Ag as a good co-catalyst to trap electrons that enhanced the activity of theMCN. Keywords: MCN; phenol; aniline, photocatalyst; silver; co-catalyst.